Faktor Risiko Nyeri Leher Non Spesifik - Pamarta, Rachel Dwyana; Setiorini, Anggi; Maulana, Muhammad; Utama, Winda Trijayanthi (Medula, 2025)
Non-specific neck pain is a form of acute, subacute, or chronic neck pain, and there is no abnormal anatomical structure as the cause of the pain. Bad posture habits are a contributing factor to non-specific neck pain. This bad posture will cause muscle tension in the neck which can increase intramuscular pressure which can reduce circulation in the joints, as well as compression of the nervous system and blood vessels around it. This ends in the emergence of pain complaints. The cause of non-specific neck pain is multifactorial consisting of several risk factors. The purpose of this study was to determine the risk factors for non-specific neck pain. The method used is article review. Searching for articles both nationally and internationally then summarizing the discussion topics and comparing the results presented in the article. Based on the review that has been done. Non-specific neck pain has a multifactorial cause consisting of several risk factors. Individual factors of non-specific neck pain include gender, age, BMI, and medical history. Work factors include duration of work, length of service, and work posture. Psychological factors include stress, depression, and lack of sleep. Environmental factors such as temperature and humidity are also risk factors for non-specific neck pain.